Buscas por estrelas jovens: Variabilidade e Binaridade - Marcelo Medeiros Guimaraes (2008)
In the attempt of increasing our knowledge about young stars, we performed three large scale surveys of two star forming regions, namely the Orion Nebula and the young OB association known as Cygnus OB2.The first survey was made with the Advanced Camera for Surveys (ACS) onboard the Hubble Space Telescope. We used a narrow band filter, centered in the wavelength of the H line, to map the region around the center of the Orion Nebula Cluster. Our main goal is to use the highresolution of the ACS (0.¡ä¡ä05 per pixel) to detect new visual binaries. We set the separation limit between the components of the system (0.¡ä¡ä15 to 1.¡ä¡ä5) using completeness tests and the probabilityof chance alignment. After a minute analysis of each system detected in our sample, we reached our goal and also observed clear evidence of the dynamical evolution of these systems in the Orion Nebula Cluster. We discovered 55 new visual binary systems within a total of 72 binariesand 3 triple systems. We determined a binary frequency of (8.8¡À1.1)% for the Orion Nebula Cluster, which is 1.5 times smaller than the frequency for the field and 2.2 times smaller than for the loose T associations. This was an already known fact but was based on small number statistics, while our results are based on more significant numbers. The ratio between wide and close binaries has a significant increase at 460¡ä¡ä from the center of the cluster, assumed to be the star 1 OriC. Our analysis indicates that this is clear evidence of the dynamical evolutionof the Orion Nebula Cluster, which happens through the destruction of wide binaries, after few passages through the cluster¡¯s potential well. A byproduct of our survey is the detection of substellar candidates. We determined the double nature of the object known as COUP1061,which is classified in the literature as a brown dwarf. This finding implies that COUP1061 is a binary system where both components are brown dwarfs, separated by ¡«100 AU. In order to perform the second and third surveys we made use of the Wide Field Camera of the United Kingdom Infrared Telescope. We observed the Orion Nebula and Cygnus OB2with near infrared filters, JHK. Our objective with these photometric surveys is to determine the population of variable stars in these star forming regions. Using statistical indices we can separate and classify the variable stars into different groups. Because these photometric surveys cover large areas in the sky we developed special routines to deal with the catalogs, which are composed of thousands and sometimes hundreds of thousands of objects. The Orion Nebula was observed during 101 nights, covering 178 days. We performed shortexposures (2 seconds long) once each night. Long cataloging and calibration processes were necessary until a satisfying dataset was ready to be used in the search for variable stars. Using statistical indices we were able to discover new eclipsing binary candidates and star withvariability due to pulsation or rotation. A long analysis process is still necessary to exhaust the huge amount of information obtained in this survey.